A pluralidade de Pessoa em filmes de animação e histórias em quadrinhos - Moura, Pedro (Pessoa Plural)
This article examines a small set of animated films and comic book stories that explore Pessoa’s themes, either through strategies of textual adaptations or by dramatizing characters drawn from Pessoa’s imagination. Due to the variety of genres, styles, and moods found in the original poems and in the comic and film texts, every object is inherently plural in its substance and diegetic levels, creating aporias that are never resolved or subsumed into a central plot or a closed logic.